Natural Antioxidants: Multiple Mechanisms to Protect Skin From Solar Radiation - Dunaway, Spencer; Odin, Rachel; Zhou, Linli; Ji, Liyuan; Zhang, Yuhang; Kadekaro, Ana L. (Frontiers in Pharmacology, 2018)
Human skin exposed to solar ultraviolet radiation (UVR) results in dramatically increased production of reactive oxygen species (ROS). The sudden increase in ROS shifts the balance towards a pro-oxidative state resulting in oxidative stress. The detrimental effects of oxidative stress occur through multiple mechanisms that involve alterations to proteins and lipids, induction of inflammation, immunosuppression, DNA damage and activation of signaling pathways that affect gene transcription, cell cycle, proliferation and apoptosis. All of these alterations promote carcinogenesis and therefore, regulation of ROS levels is critical to maintain normal skin homeostasis. Several botanical products have been found to exhibit potent antioxidant capacity and the ability to counteract the UV-induced insults to the skin. These natural products exert their beneficial effects through multiple pathways, including some known to be negatively affected by solar UVR. Aging of the skin is also accelerated by UVR exposure, in particular UVA rays that penetrate deep into the epidermis and the dermis where it causes the degradation of collagen and elastin fibers via oxidative stress and activation of matrix metalloproteinases (MMPs). Because natural compounds are capable of attenuating some of the UV-induced aging effects in the skin, increased attention has been generated in the area of cosmetic sciences. The focus of this review is to cover the most prominent phytoproducts with potential to mitigate the deleterious effects of solar UVR and suitability for use in topical application.